PENDAMPINGAN PENYUSUNAN DOKUMEN SISTEM PENJAMINAN MUTU DI STAI RAYA MLOKOREJO JEMBER - Ahmad Zarkasyi; Zaedun Na’im ('Ibadatuna : Jurnal Pengabdian Masyarakat, 2024)
The article describes assistance in improving the quality of the STAI Raya Mlokorejo Jember Study Program. The research uses constructive methods. Participants in the workshop and mentoring held on 04-06 November 2023 were 19 lecturers from three study programs. The activity was carried out 3 times. All lecturers attended the 3 meetings. However, only 11 people actively presented, asked questions, and commented regarding SPMI, SOP, AMI, and money jar. The results of this assistance provide awareness to the entire STAI academic community, Raden Abdullah Yaqin Mlokorejo, of the importance of SPMI. The academic community is committed to implementing P-P-E-P-P and its supporting components. STAI Raden Abdullah Yaqin Mlokorejo has a standard drafting team, standard implementation application, AMI learning monev, and application team, and implements RTM to improve last year's standards